TDG is a novel tumor suppressor of liver malignancies - Haider M. Hassan; Majdina Isovic; Michael Tully Underhill; Joseph Torchia (Molecular & Cellular Oncology, 2020)
In a recent publication, we demonstrated that conditional deletion of the gene encoding thymine DNA glycosylase (TDG) leads to a late onset of hepatocellular carcinoma (HCC). TDG loss causes disruption in active DNA demethylation in the liver and dysregulation of the farnesoid X receptor and small heterodimer partner (FXR-SHP) regulatory cascade. This leads to a loss of bile acid and glucose homeostasis, which predisposes mice to HCC.